From Diagnosis to Action, a look at the Multidimensional Security from Peru - Díaz Núñez, Jorge (Hemisferio - Revista del Colegio Interamericano de Defensa, 2016)
This article presents the guidelines of the current security policy in Peru, underpinning the lessons learned over the past years to face the threats of drug trafficking and terrorism that are part of our reality in an operational environment based on concepts of Multidimensional Security. This has led to dynamic processes of adaptation and joint gear setting while integrating capabilities so as to meet the state objectives of creating an enabling environment for development with social peace and understanding the urgent need to rely upon cooperation to successfully combat these threats that are global in nature as they transcend borders and directly affect the development of the Western Hemisphere.